Carrying capacity framework in reducing the waste produced in tourism area - Mohd Nasir, Nadia; Ibrahim, Mansor; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim; Hj. Baharuddin, Zainul Mukrim; Othman, Rashidi (2016)
Too many tourists on site means there will be more waste generated in the tourism site, directly or indirectly. Adding to that, the lack of waste management strategies in tourism area will lead to undesirable environmental quality. This will give bad perceptions towards the future tourist and later on will impact the tourism industry itself. Hence, the implementation of carrying capacity concept is an effort to preserve the tourism area as a sustainable tourist destination as well as maintaining its natural value. Based on existing researches, it clearly shows the success of the carrying capacity concept. However, the government and related agencies must have seen this issue further ahead. Therefore, the aim of this study is to identify the lacking of current policies and action plans by the government in managing tourism sites. This research focuses on analyzing the legal material and its action plan. A combination of descriptive and analytical approach will be done. The output of this paper is the analysis of the current policies and plans and how the gaps can be filled in order to promote sustainable tourism in Pulau Perhentian. This paper will give an added value to promote sustainable tourism in Malaysia hospitality services industry